# Find an equation of the tangent to the curve : x=sin (pi) t, y=t^2 +t at the point (0,2). Then graph the curve and the tangent.

Using the point-slope formula, an equation of the tangent to the curve x=sin (pi) t , y=t^2 +t at the point (0,2) would be y-2=-3/pi(x-0) ==> y=-3/pi x+2. A graph of the curve can be found below.

We are given a curve in parametric form:

`x=sin(pi t), y=t^2+t`

We are asked to graph the curve and then find and graph the tangent line to the curve at (0,2).

To graph the curve we can substitute in values for t. Here are a few points found by starting...

## See This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

We are given a curve in parametric form:

`x=sin(pi t), y=t^2+t`

We are asked to graph the curve and then find and graph the tangent line to the curve at (0,2).

To graph the curve we can substitute in values for t. Here are a few points found by starting at t=0 and incrementing t by .25:

(0,0), (.707,.3125), (1,.75), (.707, 1.3125), (0,2), (-.707, 2.8125), (-1,3.75), (-.707, 4.8125), (0,6)

(See attachment for curve.)

To find the tangent line we need a point (here (0,2)), and the slope of the tangent line at that point. To find the slope we need the derivative and we use `(dy)/(dx)=((dy)/(dt))/((dx)/(dt))` .

`(dy)/(dt)=2t+1; (dx)/(dt)=pi cos(pi t)`

So `(dy)/(dx)=(2t+1)/(pi cos(pi t))`

Now at (0,2) we have t=1 so `(2(1)+1)/(pi cos(pi))=-3/pi`

Using the point-slope formula for the tangent line we get:

`y-2=-3/pi(x-0) ==> y=-3/pi x+2`

(See the attachment for the graph of the tangent line.)

Images:
This image has been Flagged as inappropriate Click to unflag
Image (1 of 1)